Morphological and molecular characterization of cyst-forming nematodes on wheat from Shanxi Province - LIU Kun; XI Tian-yuan; ZHANG Yao-fang; ZHENG Jing-wu (浙江大学学报. 农业与生命科学版)
Cyst-forming nematode parasitizing on wheat is a serious problem in the world. The first report of cyst nematode infecting wheat in China was in 1989, and since then the nematodes were reported in 13 provinces of China. In Shanxi Province no systematic survey were made for the distribution and species identification of the cyst-forming nematodes parasitizing in wheat.During 2010 to 2011, an extensive survey and investigation on cyst-forming nematodes parasitizing wheat in Shanxi Province was carried out. Key morphological characteristics and morphometrics of cysts and second-stage juveniles of major populations were systematically observed and measured, and molecular data of rDNA -ITS region of the populations were analyzed.The cysts were characterized by lemon-shaped, with posterior protuberance, vulval silt short, bifenestrate, bullae present and under bridge absent. Morphometric comparison of cysts and second stage juveniles showed that all the cyst-forming nematode populations from Shanxi were Heterodera avenae. The phylogenic analysis of the rDNA-ITS sequences based on nine cereal cyst nematode (CCN) populations from Shanxi Province showed a close genetic relationship with the H. avenae populations from China including Anhui, Jiangsu, Henan, Beijing, Hebei and Qinghai, and India, and H. australis population from Australia, however, the CCN populations from China had a distant genetic relationship with H. avenae from European countries including Germany, Morocco, Spain, United Kingdom and France. Amplification of rDNA-ITS region of H. avenae populations collected from Shanxi yielded a fragment with the length of 1 045 bp.Both morphological and molecular identification of cyst-forming nematode populations parasitizing on wheat in Shanxi confirm that all the populations collected in this study are H. avenae, and no other species are detected.